Mechanical response behavior, constitutive modeling and microstructural evolution of a 7003-T6 Al alloy rolled plate under high-speed impact loading - Pengcheng Guo; Sawei Qiu; Tuo Ye; Xiao Liu; Biwu Zhu; Yuanzhi Wu; Luoxing Li (Journal of Materials Research and Technology)
7003 Al alloy rolled plate possesses outstanding mechanical characteristics such as high specific strength and good formability, so it is used to manufacture some key structures of vehicle body. Therefore, figuring out the dynamic mechanical properties and response behavior are beneficial to further broaden its application. This paper mainly focuses on the mechanical response behavior, constitutive modeling and microstructural evolution of a 7003-T6 Al alloy rolled plate under various strain rates, through high-speed impact test, constitutive modeling, numerical simulation and microscopic characterization. The results show that the flow stress exhibits a positive SRS, while a negative SRS in the later stage of deformation. When the impacted strain is lower than about 0.21, the plastic deformation is relatively uniform, followed by local shear plastic deformation, which initiates from the edge of the impact surface and then propagates to the center of sample approximately along 25°. Subsequently, local shear deformation occurs at the edge of the other end of the sample. Apparently, the original fibrous grains are continuously fibrillated with the increase of applied strain. The dislocation density increases with the increase of impact strain and strain rate, evolving into structures characterized by GNDs, near-cell dislocations, and fully developed cell dislocations. With the combined assistance of adiabatic temperature rise and dislocation evolution, lots of small pre-existing precipitates aggregate to form larger precipitates. Furthermore, an optimized JC constitutive model is established by modifying the strain hardening term into a coupled equation of strain and strain rate. The correlation coefficient R and average relative error AARE are 97.45 % and 1.51 %, respectively. Therefore, the evolution of adiabatic temperature rise is obtained by numerical simulation using this optimized model. These results can contribute to the design and optimization of vehicle body structures made by 7003 Al alloy plates in service under extreme conditions.